Variability in working memory performance explained by epistasis vs polygenic scores in the ZNF804A pathway. - ANNEY, RICHARD; GILL, MICHAEL; DONOHOE, GARY (My University, 2014)
IMPORTANCE We investigated the variation in neuropsychological function explained by risk alleles at the psychosis susceptibility gene ZNF804A and its interacting partners using single nucleotide polymorphisms (SNPs), polygenic scores, and epistatic analyses. Of particular importance was the relative contribution of the polygenic score vs epistasis in variation explained. OBJECTIVES To (1) assess the association between SNPs in ZNF804A and the ZNF804A polygenic score with measures of cognition in cases with psychosis and (2) assess whether epistasis within the ZNF804A pathway could explain additional variation above and beyond that explained by the polygenic score. DESIGN, SETTING, AND PARTICIPANTS Patients with psychosis (n = 424)were assessed in areas of cognitive ability impaired in schizophrenia including IQ, memory, attention, and social cognition.We used the Psychiatric GWAS Consortium 1 schizophrenia genome-wide association study to calculate a polygenic score based on identified risk variants within this genetic pathway. Cognitive measures significantly associated with the polygenic score were tested for an epistatic component using a training set (n = 170), which was used to develop linear regression models containing the polygenic score and 2-SNP interactions. The best-fitting models were tested for replication in 2 independent test sets of cases: (1) 170 individuals with schizophrenia or schizoaffective disorder and (2) 84 patients with broad psychosis (including bipolar disorder, major depressive disorder, and other psychosis). MAIN OUTCOMES AND MEASURES Participants completed a neuropsychological assessment battery designed to target the cognitive deficits of schizophrenia including general cognitive function, episodic memory, working memory, attentional control, and social cognition. RESULTS Higher polygenic scores were associated with poorer performance among patients on IQ, memory, and social cognition, explaining 1%to 3%of variation on these scores (range, P = .01 to .03). Using a narrow psychosis training set and independent test sets of narrow phenotype psychosis (schizophrenia and schizoaffective disorder), broad psychosis, and control participants (n = 89), the addition of 2 interaction terms containing 2 SNPs each increased the R2 for spatial working memory strategy in the independent psychosis test sets from 1.2%using the polygenic score only to 4.8%(P = .11 and .001, respectively) but did not explain additional variation in control participants. CONCLUSIONS AND RELEVANCE These data support a role for the ZNF804A pathway in IQ, memory, and social cognition in cases. Furthermore, we showed that epistasis increases the variation explained above the contribution of the polygenic score.
PUBLISHED
Keywords: adult; allele; article; attention; bipolar disorder; cognitive defect; controlled study; episodic memory; epistasis; female; gene; gene interaction; gene replication; genetic analysis; genetic association; genetic risk; genetic susceptibility; genetic variability; human; intelligence quotient; major clinical study; major depression; male; mental performance; neuropsychological test; phenotype; polygenic score; schizoaffective psychosis; signal transduction; single nucleotide polymorphism; social cognition; training; working memory; ZNF804A gene; adult; allele; article; attention; bipolar disorder; cognitive defect; controlled study; episodic memory; epistasis; female; gene; gene interaction; gene replication; genetic analysis; genetic association; genetic risk; genetic susceptibility; genetic variability; human; intelligence quotient; major clinical study; major depression; male; mental performance; neuropsychological test; phenotype; polygenic score; schizoaffective psychosis; signal transduction; single nucleotide polymorphism; social cognition; training; working memory; ZNF804A gene